2022
DOI: 10.3390/ijms23073738
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Lipids: From Membrane Organization to Apoptotic Facilitation

Abstract: Mitochondria are the most complex intracellular organelles, their function combining energy production for survival and apoptosis facilitation for death. Such a multivariate physiology is structurally and functionally reflected upon their membrane configuration and lipid composition. Mitochondrial double membrane lipids, with cardiolipin as the protagonist, show an impressive level of complexity that is mandatory for maintenance of mitochondrial health and protection from apoptosis. Given that lipidomics is an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 79 publications
1
16
0
Order By: Relevance
“…These observations indicate that the liquid order in the IMM significantly increases upon induction of apoptosis, which is consistent with that a large percentage of CLs in the IMM is oxidized by ROS during apoptosis 41 . It has been reported that oxidized CLs are immediately transferred to the OMM, where it participates in the opening of mitochondrial permeability transition pore (MPTP) and facilitates the release of cytochrome c into the cytosol, thereby inducing apoptosis 42,43 , consistent with the results obtained by light irradiation. In contrast, tubular network of mitochondria with a slightly increased fluorescence lifetime was observed when incubated under HBSS-starvation conditions for 5 h. These findings imply that fluorescence lifetime of MitoPB Red in the IMM and mitochondrial functions are correlated, and the damage level of individual mitochondria can be assessed by this method.…”
Section: Evaluation Of the Mitochondrial Staining Ability The Promine...supporting
confidence: 81%
“…These observations indicate that the liquid order in the IMM significantly increases upon induction of apoptosis, which is consistent with that a large percentage of CLs in the IMM is oxidized by ROS during apoptosis 41 . It has been reported that oxidized CLs are immediately transferred to the OMM, where it participates in the opening of mitochondrial permeability transition pore (MPTP) and facilitates the release of cytochrome c into the cytosol, thereby inducing apoptosis 42,43 , consistent with the results obtained by light irradiation. In contrast, tubular network of mitochondria with a slightly increased fluorescence lifetime was observed when incubated under HBSS-starvation conditions for 5 h. These findings imply that fluorescence lifetime of MitoPB Red in the IMM and mitochondrial functions are correlated, and the damage level of individual mitochondria can be assessed by this method.…”
Section: Evaluation Of the Mitochondrial Staining Ability The Promine...supporting
confidence: 81%
“…UTMoS 2 at 100 mg Mo/L activated the apoptotic pathway. Apoptosis is typically accompanied by the loss of membrane homeostasis . Given the significant impact of Na 2 MoO 4 on the membrane structure and its associated lipids, the role of ionic Mo release in UTMoS 2 -induced lipid disorders deserves attention.…”
Section: Resultsmentioning
confidence: 99%
“…PC and PE are major lipid components of mitochondrial membranes, and therefore, changes in their consistency are likely to influence mitochondrial physiology ( 14 , 15 ). FADS2 inhibition decreased the mitochondrial load, mitochondrial membrane potential, and oxygen consumption rate (OCR) in primary adrenocortical cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Along the same line, in vitro treatment of adrenocortical cells with SC-26196, a FADS2 inhibitor, potently reduced the abundance of PUFA, including ARA acyl chains of mitochondrial phospholipids, mainly PC and PE. These are the most abundant phospholipids in all cellular membranes including mitochondrial membranes ( 14 , 15 ) and important stores of ARA residues ( 42 – 44 ). FADS2 inhibition also reduced the mitochondrial membrane potential, oxygen consumption, and mitochondrial cholesterol uptake and diminished steroidogenesis, which was partially reversed by ARA supplementation.…”
Section: Discussionmentioning
confidence: 99%